2007
DOI: 10.1017/s0952523807070095
|View full text |Cite
|
Sign up to set email alerts
|

Complex motion selectivity in PMLS cortex following early lesions of primary visual cortex in the cat

Abstract: In the cat, the analysis of visual motion cues has generally been attributed to the posteromedial lateral suprasylvian cortex (PMLS) (Toyama et al., 1985; Rauschecker et al., 1987; Rauschecker, 1988; Kim et al., 1997). The responses of neurons in this area are not critically dependent on inputs from the primary visual cortex (VC), as lesions of VC leave neuronal response properties in PMLS relatively unchanged (Spear & Baumann, 1979; Spear, 1988; Guido et al., 1990b). However, previous studies have used a limi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 70 publications
0
3
0
Order By: Relevance
“…7, Boyd and Matsubara, 1999;Shipp and Grant, 1991), the majority (∼70%) of which exhibit some degree of directional-selectivity, a higher proportion than among all cells (∼55%) residing in the upper layers of area 17 (Sherk, 1989), suggesting that the projection contributes to the role of area PMLS in motion perception (Lomber et al, 1996;Rudolph and Pasternak, 1996) and its preponderance (∼ 80-90%) of direction-selective neurons (Spear and Baumann, 1975). Indeed, selective removal of the projection by unilateral lesion of area 17 has been reported to reduce the proportion and degree of directionselectivity among PMLS cells for both simple (Spear, 1988) and complex (Ouellette et al, 2007) motion stimuli.…”
Section: Functional Implicationsmentioning
confidence: 99%
“…7, Boyd and Matsubara, 1999;Shipp and Grant, 1991), the majority (∼70%) of which exhibit some degree of directional-selectivity, a higher proportion than among all cells (∼55%) residing in the upper layers of area 17 (Sherk, 1989), suggesting that the projection contributes to the role of area PMLS in motion perception (Lomber et al, 1996;Rudolph and Pasternak, 1996) and its preponderance (∼ 80-90%) of direction-selective neurons (Spear and Baumann, 1975). Indeed, selective removal of the projection by unilateral lesion of area 17 has been reported to reduce the proportion and degree of directionselectivity among PMLS cells for both simple (Spear, 1988) and complex (Ouellette et al, 2007) motion stimuli.…”
Section: Functional Implicationsmentioning
confidence: 99%
“…The cat is one of the most studied models of infant-lesion–induced cerebral reorganization and sparing of function (Payne & Lomber, 2002; Spear, 1995; Villablanca, Schmanke, & Hovda, 1999) and has been used to demonstrate that lesions of primary visual cortex at postnatal day 1 (P1) produces rewiring of visual circuits (Kalil, Tong, & Spear, 1991; Lomber, MacNeil, & Payne, 1995; Lomber, Payne, Cornwell, & Pearson, 1993; Payne & Lomber, 1998) and alterations in their metabolic capacities and physiological properties (Desautels & Casanova, 2001; Guido, Spear, & Tong, 1992; Ouellette, Minville, Boire, Ptito, & Casanova, 2007; Spear, Tong, & McCall, 1988); overall, this reorganization serves to produce a blurring of the ordinarily sharp cerebral localization of function (Lomber & Payne, 2001) and correlates with a higher degree of functional recovery in P1-lesioned animals than in adults with equivalent brain damage (Hovda & Villablanca, 1990; Payne, 2003; Payne & Cornwell, 1994).…”
mentioning
confidence: 99%
“…These residual visual functions are likely mediated through plastic reorganization of visual pathways after lesions (Payne, 2004;Rushmore and Payne, 2004;Rushmore et al, 2008;, as demonstrated by previous morphological studies on post-lesion rewiring of visual circuits capable of mediating visual abilities (Kalil et al, 1991;Lomber et al, 1993Lomber et al, , 1995Payne& Lomber, 1998). Previous research found that a significant portion of neurons in posteromedial lateral suprasylvian (PMLS) cortex were responsive to moving gratings as well as simple and complex random dot kinematograms (RDKs) following early lesions of primary visual cortex in cats (Ouellette et al, 2007). This is consistent with other observations done in primates, which showed that neurons in the lesion-projection zones of MT (middle temporal area) and even V2, V3 and V4 can be activated by visual stimulation after damage of primary visual cortex (Azzopardi et al, 2003;Schmid et al, 2009;Schmid et al, 2010) as certain regions in the extrastriate visual cortex may have direct connections with subcortical nucleus and thus form parallel, V1-bypassing pathways contributing to the behavioral phenomenon of blindsight.…”
Section: Discussionmentioning
confidence: 99%